Analysis of synthetic cannabinoids on paper before and after processing for latent print using DFO and ninhydrin. (December 2019) - Caterino, Jacquelyn; Clark, Jason; Yohannan, Joshua C.
Highlights: Synthetic cannabinoids on paper are being encountered more often. Synthetic cannabinoids are becoming an issue in prisons and jails, effecting prisoners and also staff. Latent print processing of porous substrates. Abstract: There have been several cases in the news regarding the presence of synthetic cannabinoids on paper being smuggled into jails and prisons in the United States. The Allegheny County Office of the Medical Examiner has been involved in the analysis of multiple cases. For the first time the laboratory received an analysis request for not only identification of controlled substances, but also for the presence of latent fingerprints. It was unknown if the processing methods used by the latent print unit would interfere with the identification of the controlled substances. This paper shows that DFO and ninhydrin processing will remove some of the synthetic cannabinoids, possibly effecting concentration on the paper, but the substances were still able to be positively identified after processing.